2017
DOI: 10.1016/j.nuclphysa.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for chiral symmetry restoration in heavy-ion collisions

Abstract: We study the effect of the chiral symmetry restoration (CSR) on heavy-ion collisions observables in the energy range √ s NN = 3-20 GeV within the Parton-Hadron-String Dynamics (PHSD) transport approach. The PHSD includes the deconfinement phase transition as well as essential aspects of CSR in the dense and hot hadronic medium, which are incorporated in the Schwinger mechanism for particle production. Our systematic studies show that chiral symmetry restoration plays a crucial role in the description of heavy-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This regime was abruptly terminated when the system evolved through a partonic phase at energies above √ s N N ∼ 7-10 GeV, resulting in a rather sharp drop of the K + /π + ratio as a result of the chiral condensate melting and QGP formation during the collision. This microscopic transport model also predicts a smoothing of the peak with decreasing system size [45] albeit not quite matching the behaviour recently observed by NA61 in Ar+Sc collisions [42].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This regime was abruptly terminated when the system evolved through a partonic phase at energies above √ s N N ∼ 7-10 GeV, resulting in a rather sharp drop of the K + /π + ratio as a result of the chiral condensate melting and QGP formation during the collision. This microscopic transport model also predicts a smoothing of the peak with decreasing system size [45] albeit not quite matching the behaviour recently observed by NA61 in Ar+Sc collisions [42].…”
Section: Introductionsupporting
confidence: 73%
“…In another, purely hadronic transport model, the basic pattern of the energy scan of strange-to-nonstrange particle production ratios including the K + /π + and the Λ/π − horns could be reproduced because the lifetime of the (hadronic) fireball until freezeout gets shortened when increasing the energy of the collision above 30 AGeV [43]. A rather successful theoretical description of the experimental data could be given within yet another transport approach, the parton-hadron-string-dynamics (PHSD) approach [44,45] where strangeness production in the hadronic phase was enhanced by a modification of the Schwinger production rates due to partial chiral symmetry restoration. This regime was abruptly terminated when the system evolved through a partonic phase at energies above √ s N N ∼ 7-10 GeV, resulting in a rather sharp drop of the K + /π + ratio as a result of the chiral condensate melting and QGP formation during the collision.…”
Section: Introductionmentioning
confidence: 99%
“…The description of the K + /π + at energies < 8 GeV has not such a clear explanation. From one hand it was shown that the partial chiral symmetry restoration could be responsible for the quick increase in the K + /π + ratio at low energies and its decrease with increasing energy (as a result of chiral condensate destruction) [2,3]. From other hand it is not clear still if the deconfinement appeared during heavy ion collision at such energies and if it coincided with the chiral phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…A rather successful theoretical description of the experimental data could be given within yet another transport approach, the parton-hadron-string-dynamics (PHSD) approach [44,45] where strangeness production in the hadronic phase was enhanced by a modification of the Schwinger production rates due to partial chiral symmetry restoration. This regime was abruptly terminated when the system evolved through a partonic phase at energies above √ s N N ∼ 7−10 GeV, resulting in a rather sharp drop of the K + /π + ratio as a result of the chiral condensate melting and QGP formation during the collision.…”
Section: Introductionmentioning
confidence: 99%